ijps 2020
DOI: 10.36468/pharmaceutical-sciences.621
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biological Evaluation and Molecular Docking Studies of Novel 1,8-Naphthyridine-3-carboxylic Acid Derivatives as Potential Antimicrobial Agents (Part-1)

Abstract: This is an open access article distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 3.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as the author is credited and the new creations are licensed under the identical terms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Due to a broad spectrum of biological actions previously mentioned, 1,8-naphthyridine derivatives have gained increasing importance in the fields of medicinal chemistry and drug development. Studies indicate that these compounds have enormous potential for the synthesis of new molecules, which has been associated with the structure–activity relationship in several biological models [ 11 , 12 , 13 , 14 , 15 , 16 ]. Furthermore, molecular modifications can be used to improve the physicochemical properties of these substances, generating compounds with optimized therapeutic effects [ 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to a broad spectrum of biological actions previously mentioned, 1,8-naphthyridine derivatives have gained increasing importance in the fields of medicinal chemistry and drug development. Studies indicate that these compounds have enormous potential for the synthesis of new molecules, which has been associated with the structure–activity relationship in several biological models [ 11 , 12 , 13 , 14 , 15 , 16 ]. Furthermore, molecular modifications can be used to improve the physicochemical properties of these substances, generating compounds with optimized therapeutic effects [ 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen-containing heterocycles include both chemically synthesized and naturally occurring compounds such as 1,8-naphthyridine derivatives [ 10 ]. Studies have shown that these compounds have various biological activities such as antibacterial [ 11 ], antifungal [ 12 ], antiviral [ 13 ], anti-inflammatory [ 14 ], antitumor [ 15 ], and analgesic [ 16 ], and are therefore promising candidates for the development of new drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Melting point was recorded on electro thermal CIA9300 melting point apparatus. The Proton nuclear magnetic resonance ( 1 HNMR) to identify the structure and 13 CNMR spectra were recorded on nucleic magnetic resinous model ultra shield 400MHZ, Bruker Co, Germany using TMS as internal reference and DMSO-d6 as solvent . IR spectra were recorded on infrared spectrophotometer model Tensor 27.Bruker Co. Germany by using KBr disc .…”
Section: Materials and Methods 21 Instrumentationmentioning
confidence: 99%
“…The reaction of phenyl hydrazine with chalcones (4,5) afforded compounds (12,13) (scheme-4-) . The IR spectra of these compounds (12,13) showed absorption at (1595 cm -1 and 1591 cm -1 ) for C=N group respectively . H 1 NMR spectra of these compounds showed a single signal at δ 5.31 and δ 5.31 for hydrogen in the pyrazoline ring .…”
Section: Scheme -2 -mentioning
confidence: 97%
See 1 more Smart Citation